ANALISA INDEKS DAN SEBARAN KEKERINGAN MENGGUNAKAN METODE STANDARDIZED PRECIPITATION INDEX (SPI) DAN GEOGRAPHICAL INFORMATION SYSTEM (GIS) UNTUK PULAU LOMBOK - Humairo Saidah; M Bagus Budianto; Lilik Hanifah (JURNAL SPEKTRAN, 2017)
Since rainfall and surface water availability is limited, Lombok island has high risk drought. Drought causes poverty due to its close corellation to desease spread and lack of food. So it needs to recognize drought characteristic for early anticipation and adaptation. Standardized Precipitation Index is the method to be used to determine rainfall deviation from its normal depth. SPI was chosen because of its simplicity and ability to count the index of drought and figure its grade. Data for this analyses was taken from 1996-2015 of rainfall station entire Lombok Island, then the result figured out in a drought map using Arc GIS. The result of this study shows that the severest drought for annually deficit period indexed -3.25 was happened at Lingkuk Lime on 2002, then for 6 monthly deficit period indexed -4.97 happened at Sekotong on July-December 2000, afterwards for 3 monthly deficit period indexed -4.72 happened at Loang Make on Pebruary-April 2002, later for monthly deficit period indexed -4.99 happened at Jurang Sate on January 2015. Keywords: drought index, deficit period, SPI, Arc GIS.